An Experimental Study on the Deformation and Strength Characteristics of Q3 Loess under a Plain Strain Anisotropic Consolidation Condition - Yu Zhang; Yang Zhao; Jin Liu; Tian-Yi Meng; Sheng-Jun Shao; Fang-Tao She (Advances in Civil Engineering)
To study the strength, deformation characteristics, and intermediate principal stress of intact loess, vertical loading stress tests with different initial stress state k value were conducted under different confining pressures. Plane strain tests were carried out by the transformed true triaxial apparatus of Xi’an University of Technology. The study shows that loess tends to be in a plastic failure state in different confining pressures and k values, and the stress-strain relationship curve is of a hardening type. Results reveal that loess lateral and volume deformations have nonlinear relationships with its vertical deformation, and volume deformation shrinks in the process of shearing. The effect of confining pressure on soil deformation is greater than k value. The intermediate principal stress coefficient decreases with the increase of the confining pressure and transforms from increasing to decreasing with the increase of k value (ranging from 0.2 to 0.4). In brief, the loess failure strength is closely related to k value, confining stress, and spherical stress state. When k value increases, cohesion effect reduces, whereas internal friction angle increases linearly. The influence of k value on soil strength and deformation is closely related to confining pressure.